2016
DOI: 10.21776/ub.jpacr.2016.005.03.279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ni/Hydrotalcite and Its Application in Hydrocracking Calophyllum Inophyllum Oil

Abstract: This research aims to synthesize hydrotalcite as an alternatives of catalyst support of hydrocracking of vegetable oils. Hydrotalcite can be synthesized in several ways, the most common is coprecipitation method. Hydrotalcite was synthesized using Mg/Al mole ratio of 1: 1, NaOH and Na 2 CO 3 as base solutions. Ni/hydrotalcite catalyst was synthesized by incipicient wetness impregnation method with Ni impregnation of 10% w/w. The characterization of the crystal structure was determined by X-ray diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Application of Mg-Al hydrotalcite is support catalyst which had basicity and large specific surface area that suitable for transesterification reaction. In previous research [18], Mg-Al hydrotalcite with Mg/Al molar ratio 1:1 as a supported catalyst had increasing acidity so that suitable for hydrocracking reaction.…”
Section: Introductionmentioning
confidence: 96%
“…Application of Mg-Al hydrotalcite is support catalyst which had basicity and large specific surface area that suitable for transesterification reaction. In previous research [18], Mg-Al hydrotalcite with Mg/Al molar ratio 1:1 as a supported catalyst had increasing acidity so that suitable for hydrocracking reaction.…”
Section: Introductionmentioning
confidence: 96%
“…The oxygenated compounds containing carboxylic acid of 4.16 area% were found [5]. Marlinda et al reported that n-C 15 and n-C 17 were the main abundant hydrocarbon compounds in biofuel produced through hydrocracking on Cerbera manghas oil at temperature of 350 o C and pressure of 15 bar for 2 h with Co(0.88)-Ni(3.92)/HZSM-5 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Estes minerais podem ocorrer em ambientes como depósitos salinos, o que comprova que altas temperaturas e pressões não são extremamente necessárias para a formação de estruturas HDL estáveis (CREPALDI et al, 1998;BRAVO-SUÁREZ et al, 2004;NIU et al, 2016;JATAV et al, 2016). (BELLOTO et al, 1996;ZHOU et al, 2016;HAFSHAH et al;BHANAWASE & YADAV, 2017;DEBEK, et al, 2017).…”
Section: Introductionunclassified
“…The results of thermal analysis, X-ray diffractometry and infrared spectroscopy show that the composition changes aspects of crystallinity and thermal stability and allowed to clarify how some aspects such as interlamellar hydration and hydroxyl network stability correlate with the presence of cations modifiers. KEYWORDS: anionic clay, LDH, turbostratic effect.As argilas aniônicas com estrutura de Hidróxido Duplo Lamelar (HDL) são amplamente investigadas como adsorventes aniônicos e matrizes para catalisadores(TIMOFEEVA et al, 2016;ZHOU et al, 2016;HAFSHAH et al;BHANAWASE & YADAV, 2017;DEBEK, et al, 2017). A composição mais investigada é conhecida como Hidrotalcita e é baseada na estrutura do mineral brucita Mg(OH) 2 , mas com o cátion de magnésio parcialmente substituído por cátions trivalentes, comumente o alumínio(SHEN et al, 1994; DEL ARCO et al, 1999; CARPANI et al,…”
unclassified